Clinical value of early assessment of hyperfibrinolysis by rotational thromboelastometry during postpartum hemorrhage for the prediction of severity of bleeding: A multicenter prospective cohort study in the Netherlands - Marije Tahitu; Paul I. Ramler; Ada Gillissen; Camila Caram‐Deelder; Dacia D. C. A. Henriquez; Moniek P. M. deMaat; Johannes J. Duvekot; Jeroen Eikenboom; Kitty W. M. Bloemenkamp; Thomas van denAkker; Johanna G. van derBom (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction Coagulopathy may be the result of hyperfibrinolysis and could exacerbate bleeding following childbirth. Timely recognition of hyperfibrinolysis during the earliest stages of postpartum hemorrhage could identify women at risk of more severe blood loss who may benefit from targeted anti‐fibrinolytic therapy. Rotational thromboelastometry (ROTEM®) is a point‐of‐care test that could detect hyperfibrinolysis. The aim of this study was to evaluate whether early assessment of hyperfibrinolysis by ROTEM during postpartum hemorrhage could predict progression to severe postpartum hemorrhage. Material and methods During a prospective cohort study in the Netherlands among women with postpartum hemorrhage (total blood loss at least 1000 ml within 24 h after childbirth) ROTEM measurements were performed following 800–1500 ml of blood loss. Hyperfibrinolysis was defined as an enzymatic fibrinolysis index (ROTEM EXTEM maximum clot lysis [ML] minus the ROTEM APTEM ML) above 15%. Severe postpartum hemorrhage was defined as a composite end point of total blood loss greater than 2000 ml, transfusion of four or more units of packed cells, and/or need for an invasive intervention. The predictive value of hyperfibrinolysis for progression to severe postpartum hemorrhage was assessed by area under the receiver operating curve (AUC) and positive and negative predictive values. Trial registration: ClinicalTrials.gov (NCT02149472). Results Of 390 women included, 82 (21%) had severe postpartum hemorrhage. Four (1%) women had thromboelastometric evidence of hyperfibrinolysis, of whom two developed severe postpartum hemorrhage. The AUC for enzymatic fibrinolysis index more than 15% for progression to severe postpartum hemorrhage was 0.47 (95% CI 0.40–0.54). Positive and negative predictive values for this index were 50.0% (95% CI 6.8–93.2) and 79.3% (95% CI 74.9–83.2), respectively. Conclusions Thromboelastometric evidence of hyperfibrinolysis was rare in women with postpartum hemorrhage when assessed between 800 and 1500 ml of blood loss. The clinical predictive value of viscoelastometric point‐of‐care testing for hyperfibrinolysis for progression to severe postpartum hemorrhage during early postpartum hemorrhage is limited.